Hubungan Dukungan Keluarga dan Self Efficacy terhadap Tingkat Resiliensi pada Pasien Stroke - Fadila Ananda; Dwi Retno Sulistyaningsih; Indah Sri Wahyuningsih (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Stroke causes various physical, psychological, and social changes that may reduce a patient’s ability to adapt. Resilience plays a crucial role in helping patients manage their condition after a stroke. Family support and self-efficacy are important factors that can strengthen resilience; however, the level of resilience varies among individuals. Therefore, it is necessary to examine the relationship between family support, self-efficacy, and resilience among stroke patients. To determine the relationship between family support and self-efficacy with the level of resilience among stroke patients at Sultan Agung Islamic Hospital, Semarang. This study employed a quantitative correlational design with a cross-sectional approach. A total of 114 respondents were included using a total sampling technique. The instruments used were the Family Support Questionnaire, the Stroke Self-Efficacy Questionnaire, and the Connor–Davidson Resilience Scale. Data were analyzed using the Spearman Rank correlation test. The findings revealed a significant relationship between family support and resilience (p = 0.000; r = 0.665), indicating a strong positive correlation. Self-efficacy and resilience (p = 0.000; r = 0.851), indicating a very strong positive correlation. These results show that higher family support and higher self-efficacy are associated with better resilience in stroke patients. There is a significant and strong relationship between family support and self-efficacy with the level of resilience among stroke patients. Increased family support and stronger self-efficacy contribute to higher resilience in managing post-stroke conditions.